Study on Wonn Defect in 6061 Aluminum Alloy Friction Stir Welded Plates - Ahmad Radzi, Ahmad Khalil (Universiti Teknologi Petronas, 2011)
Friction stir welding (FSW) is a solid-state joining process where the original characteristics of metal remain unchanged. The technique results in high joint strength compared with other welding techniques. It has been widely used fur joining aluminum alloys in the fields of aerospace, marine, automotive, rail and many other applications of commercial importance [1]. Some important process parameters that should be taken into account and control the quality of the weld are the tool spindle speed (rpm), transverse speed (nun/min), plunging speed (nun/min), dwell time (s) and depth of penetration (mm). Studies have shown that during FSW, wormhole (tunnel) defect form along the welded area and the evolved microstructure strongly affects the mechanical properties of the joint. In this investigation, an attempt has been made to understand the influence of welding parameters on worm defect in 6061 aluminum alloy plates. For this project, nine (9) different set of welding parameter combination were used to fubricate the FSW joints. The scope of study is to butt joined two (2) pieces of 6061 aluminum alloy plates having the dimension of lOOmm x lOOmm x lOmm and by rigidly clamped both pieces to perform the welding operation. The project will fucus on tapered pin tool design using AISI H13 Tool Steel Grade. The welding tool will be fubricated using BridgePort PowerPath 15 (CNC Lathe Machine) and undergo heat treatment to increase the hardness level. Meanwhile, the welding process will be conducted using BridgePort VMC 2216 (CNC Milling Machine). By using Optical Microscope (OM), the size worm defect is measured. Microhardness measurements were taken on cross sections of the specimen and were correlated with the size of wormhole defect. The result concludes that increase in ratio of tool transverse feed rate (S) to tool spindle speed (N) will result in increase in the wormhole size (mm2) and decrease in Vickers Microhardness (HV) value.